Needs analysis of physics e-module based on hybrid-PBL model on critical thinking skills improvement - Fitri Rahmawati; Sarwanto Sarwanto; Sri Budiawanti (Momentum: Physics Education Journal, 2021)
The purpose of this study was to determine the need for teaching materials in the form of physics e-module based on Hybrid-PBL model in schools. This research applied a descriptive method. Data were collected using a needs analysis questionnaire with 14 respondents of physics teachers spread across several regions in Indonesia and 36 respondents of class XI students in SMA Negeri 2 Sragen. Based on the results of the questionnaire, the teachers indeed need teaching materials in the form of e-module and all teachers also agree that the Hybrid-PBL model can be applied in physics learning. Students are also interested in learning physics using teaching materials that can display images, videos, animations, and simulations as well as learning by involving problems in the surrounding environment. So it can be concluded that teachers and students need a physics e-module based on Hybrid-PBL model.